High-Rate Sulfate Removal Coupled to Elemental Sulfur Production in Mining Process Waters Based on Membrane-Biofilm Technology - Schwarz, Alex; Gaete, María; Nancucheo, Iván; Villa-Gomez, Denys; Aybar, Marcelo; Sbárbaro, Daniel (Frontiers in Bioengineering and Biotechnology, 2022)
It is anticipated that copper mining output will significantly increase over the next 20 years because of the more intensive use of copper in electricity-related technologies such as for transport and clean power generation, leading to a significant increase in the impacts on water resources if stricter regulations and as a result cleaner mining and processing technologies are not implemented. A key concern of discarded copper production process water is sulfate. In this study we aim to transform sulfate into sulfur in real mining process water. For that, we operate a sequential 2-step membrane biofilm reactor (MBfR) system. We coupled a hydrogenotrophic MBfR (H2-MBfR) for sulfate reduction to an oxidizing MBfR (O2-MBfR) for oxidation of sulfide to elemental sulfur. A key process improvement of the H2-MBfR was online pH control, which led to stable high-rate sulfate removal not limited by biomass accumulation and with H2 supply that was on demand. The H2-MBfR easily adapted to increasing sulfate loads, but the O2-MBfR was difficult to adjust to the varying H2-MBfR outputs, requiring better coupling control. The H2-MBfR achieved high average volumetric sulfate reduction performances of 1.7-3.74 g S/m3-d at 92-97% efficiencies, comparable to current high-rate technologies, but without requiring gas recycling and recompression and by minimizing the H2 off-gassing risk. On the other hand, the O2-MBfR reached average volumetric sulfur production rates of 0.7-2.66 g S/m3-d at efficiencies of 48-78%. The O2-MBfR needs further optimization by automatizing the gas feed, evaluating the controlled removal of excess biomass and S0 particles accumulating in the biofilm, and achieving better coupling control between both reactors. Finally, an economic/sustainability evaluation shows that MBfR technology can benefit from the green production of H2 and O2 at operating costs which compare favorably with membrane filtration, without generating residual streams, and with the recovery of valuable elemental sulfur.